Analysis of the Influence of Marketing Mix on Student Purchasing Decisions at the FEB Udayana University Canteen - Simanjuntak, Adrian Filemen; Tresnawati, Ni Kadek (The Journal of Management, Digital Business, and Entrepreneurship, 2023)
This study aims to identify the influence of marketing mix (product, price, promotion and location on students' purchasing decisions in the FEB Udayana University canteen. This study aims to understand students' preferences in choosing food and drinks in the FEB Udayana University canteen, as well as what factors most influence their purchasing decisions. In this study, the product is measured from the taste of the products offered, the varied menu, the immediacy of food and drink ingredients and the cleanliness of the canteen itself. Price is measured from an affordable price, according to students' pockets, the price applied according to the comfort of the canteen and according to the quality of the product. Promotion is measured by the way the canteen carries out mouth to mouth promotion and advertising. The location variable is measured from the location of the canteen which can be easily reached, seen, the availability of sufficient parking space and the comfort of the place. While purchasing decisions are measured from students' desire to know, try, and consider buying the product. This study uses a quantitative method with data collected through a questionnaire, then analyzed using the classical assumption test and multiple linear regression using the SPSS program. The results of the analysis show that product, price, promotion, do not influence purchasing decisions while location has a positive influence on purchasing decisions. However, simultaneously or together, variable X (Product, Price, Promotion, Location) has an influence on variable Y (Purchasing Decision).